Limb heaviness as a sensorimotor disorder alters rehabilitation adherence after a stroke - Chen, Yuanyuan; Yang, Hongyan; Chen, Yanqin; Wei, Hui; Lan, Meijuan (Frontiers in Neurology, 2022)
Introduction To the best of our knowledge, it is still unknown how perceived limb heaviness affects rehabilitation adherence. As rehabilitation adherence is very important for the functional recovery of patients with stroke, it is important to explore the relationship between perceived limb heaviness and rehabilitation adherence. Methods We retrospectively reviewed the data of patients with consecutive stroke recruited in the CIRCLE study. The influence of age, gender, time from onset to enrollment, educational background, hypertension, diabetes, Modified Rankin Scale (MRS), and National Institutes of Health Stroke Scale (NIHSS) on rehabilitation adherence was analyzed. Multiple linear regression analysis was used to examine the association between perceived limb heaviness and rehabilitation adherence changes. Results A total of 108 participants completed the study. About 40 (37.0%) participants felt limb heaviness. The mean scores on the Medical Research Council (MRC) scale for the upper affected limb strength were 3.05 ± 1.7, and the mean score on the exercise adherence questionnaire (EAQ) was 34.27 ± 8.9. Univariate analysis showed that rehabilitation adherence levels differed in upper limb muscle strength and whether they perceived limb heaviness. After adjustment for independent predictors, we found that perceived limb heaviness was associated with rehabilitation adherence (B = −9.681 ± 1.494, p < 0.05) and R2 was 0.332 and 0.074 if the muscle strength of the upper limb and perceived limb heaviness were included in the model and the model was without perceived limb heaviness, respectively. Conclusion By identifying patients with stroke with limb heaviness, it led to lower levels of motor functional rehabilitation adherence. We must pay more attention to limb heaviness and provide effective interventions to improve rehabilitation adherence and promote patient recovery.